Th17 and Cognitive Impairment: Possible Mechanisms of Action - Cipollini, Virginia; Anrather, Josef; Orzi, Francesco; Iadecola, Costantino (Frontiers in Neuroanatomy, 2019)
T helper 17 (Th17) cells represent a distinct population of immune cells, important in the defense of the organism against extracellular infectious agents. Because of their cytokine profile and ability to recruit other immune cell types, they are highly proinflammatory and are involved in the induction of several autoimmune disorders. Accumulating evidence suggests that Th17 cells and their signature cytokine IL-17 have also a role in a wide variety of neurological diseases, however the mechanisms by which they exert their pathogenic effect have not been completely elucidated. This review will briefly summarize the evidence linking Th17 cells to brain diseases associated with cognitive impairment, including multiple sclerosis, ischemic brain injury and Alzheimer’s disease. We will also investigate the mechanisms by which these cells enter the brain and induce brain damage, including direct effects of IL-17 on brain cells and indirect effects mediated through disruption of the blood-brain barrier, neurovascular dysfunction and gut-brain axis. Finally, therapeutic prospects targeting Th17 cells and IL-17 will be discussed.